New Testament text and language a Sheffield reader - Porter, Stanley E. 1956-; Evans, Craig A. (Sheffield, UK Sheffield Academic, 1997)
Includes bibliographical references and indexes.
Articles originally published in The Journal for the study of the New Testament.
Keywords: Bible. N.T. -- criticism, interpretation, etc